Peripheral Nerve Injury Induces Dynamic Changes of Tight Junction Components - Wang, Xinghui; Miao, Yang; Ni, Jun; Wang, Yaxian; Qian, Tianmei; Yu, Jun; Liu, Qianyan; Wang, Pan; Yi, Sheng (Frontiers in Physiology, 2018)
Tight junctions seal off physical barriers, regulate fluid and solute flow, and protect the endoneurial microenvironment of the peripheral nervous system. Physical barriers in the peripheral nervous system were disrupted after nerve injury. However, the dynamic changes of tight junction components after peripheral nerve injury have not been fully determined yet. In the current study, by using previously obtained deep sequencing outcomes and bioinformatic tools, we found that tight junction signaling pathway was activated after peripheral nerve injury. The investigation of the temporal expression patterns of components in tight junction signaling pathway suggested that many claudin family members were down-regulated after nerve injury. Moreover, we examined the effects of matrix metalloproteinases 7 and 9 (MMP7 and MMP9) on tight junction genes both in vitro and in vivo and found that MMP7 and MMP9 modulated the expressions of genes coding for claudin 1, claudin 10, and claudin 22. Our study revealed the dynamic changes of tight junction components after peripheral nerve injury and thus might contribute to the understanding of the molecular mechanisms underlying peripheral nerve injury and regeneration.